Bioinspired catecholic flame retardant nanocoating for flexible polyurethane foams - Cho, Joon Hee; Vasagar, Vivek; Shanmuganathan, Kadhiravan; Jones, Amanda R.; Nazarenko, Sergei; Ellison, Christopher J. (Chemistry of Materials, 2015)
An efficient, environmentally friendly, and water-applied flame retardant surface nanocoating based on polydopamine (PDA) was developed for foamed materials such as polyurethane (PU). The PDA nanocoating, deposited by simple dip-coating in an aqueous dopamine solution, consists of a planar sublayer and a secondary granular layer structure that evolve together, eventually turning into a dense, uniform, and conformal layer on all foam surfaces. In contrast to flexible PU foams that are known to be highly flammable without flame retardant additives, micro combustion calorimetry (MCC) and thermogravimetric analysis (TGA) confirm that the neat PDA is relatively inflammable with a strong tendency to form carbonaceous, porous char that is highly advantageous for flame retardancy. By depositing nano coatings of PDA onto flexible PU foams, the flammability of the PU foam was significantly reduced with increasing coating thickness. For the thickest coating (3 days of PDA deposition), the foam quickly self-extinguished and its original shape was completely preserved after exposure to a flame in a torch burn test. In addition to the char forming ability of PDA, it is hypothesized that its catechol units likely scavenge nearby radicals that typically evolve additional fuel for the fire as they attack surrounding materials. This multiple flame retardancy action of PDA (i.e., char formation + radical scavenging) enables flame retardant foams with a peak heat release rate (P-HRR) that is significantly reduced (up to 67%) relative to control foams, representing much better performance than many conventional additives reported in the literature at comparable or higher loadings.